Synthesis and self-organization properties of copolyurethanes based on perylenediimide and naphthalenediimide units - Jancy, B.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A series of perylene and naphthalene diimide-containing random copolyurethanes with different ratios of perylene/naphthalene diimide content was synthesized and characterized. Copolymerization improved the solubility of these rigid aromatic diimides, and the copolymers were soluble in common organic solvents like chloroform, tetrahydrofuran, and so forth. The absorption spectra of perylene-based copolymers showed a red-shifted peak at a wavelength of 557 nm corresponding to J-type aggregates. For naphthalene copolymers, the quenching of fluorescence at higher naphthalene incorporation suggested the presence of aggregates because of the extensive pi-pi stacking of the aromatic core. FTIR spectroscopic analysis showed that the hydrogen bonding tendency of the polymer decreased with increase in perylene/naphthalene incorporation. The fluorescence spectra of the perylene polymers were exactly a mirror image of the absorption spectra. The fluorescence spectra of the naphthalene polymers at higher naphthalene incorporation showed a red-shifted excimer like emission peak, which was assigned as static excimers based on their excitation spectra. These polymers could exhibit two types of secondary interaction modes, namely, hydrogen bonding (via urethane linkage) and pi-stacking (via aromatic perylene or naphthalene units) thus highlighting the importance of polymer design in inducing self-organization at both low and high incorporation of the rigid bisimide moieties. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polyrn Chem 47: 1224-1235, 2009
Keywords: fluorescence; hydrogen bonding; naphthalene diimide polymers; polyurethane copolymer; self-organization; structure-property relations